Self-medication Practice and its Potential Determinants among Riverine-Island’s People in Sirajganj, Bangladesh: A Cross-Sectional Study - Jamil, Safayet; Bari, Quazi Istiaque; Akhter, Asma; Hasan, Mahdi; Mukul, Md Emdadul Hasan; Rashid, Parisa Tamannur; Hossain, Md Jamal (Bangladesh Pharmaceutical Journal, 2023)
The objective of this study was to investigate the prevalence of self-medication practice and associated risk factors among riverine-island’s people in Sirajganj, Bangladesh. This study was done by following cross-sectional method with close-ended questionnaire. Data were collected from a total of 459 respondents via face-to-face interview. Frequency analysis was done to identify the prevalence of selfmedication practice, and chi-square test and logistic regression analysis were conducted for identifying the associated factors with self-medication practice. Total 83% participants were self-medicated. Notably, 62% people were self-medicated with antibiotics. More than 30% people practiced with selfmedication due to high cost of doctor consultation. Age, gender, marital status, educational status, occupation, monthly family income, and suffering from illness were correlated with self-medication practice in chi-square (χ2) analysis. Gender (male vs. female, odds ratio [OR]: 0.49, 95% confidence interval (CI): 0.25-0.95, p=0.031) and marital status (married vs. unmarried, OR: 0.43, 95% CI: 0.23- 0.83, p=0.011) were significantly associated with self-medication practice in logistic regression analysis. The rate at which persons living on riverine islands engage in self-medication is alarmingly high, and the consequence of this behavior is concerning. The inappropriate use of antibiotics is a source of concern. In order to reduce the practice of self-medication among people living on riverine islands in Sirajganj, Bangladesh, there is an immediate need to raise public awareness about the harmful effects of the practice as well as to implement appropriate legislation and activities. Bangladesh Pharmaceutical Journal 26(1): 79-88, 2023 (January)